Are We Essential, or Sacrificial? The Effects of Felt Public Gratitude on Essential Worker Recovery Activities During COVID-19. Issue 2 (March 2023) - Kim, Hee Young; Kim, Sijun; Howell, Taeya M.; Doyle, Sarah P.; Pettit, Nathan C.; Bizzarro, Michael
COVID-19 has been characterized by unprecedented levels of public gratitude to some, but not all, essential workers. In this research, we integrate insights from the stigmatized occupations and gratitude literature to build theory on the positive and negative relationships between such displays of public gratitude and essential workers' recovery activities. We argue that felt public gratitude positively relates to adaptive recovery activities (e.g., exercise) and negatively relates to maladaptive recovery activities (e.g., overdrinking). We further explain how felt public gratitude impacts (mal)adaptive recovery activities through (a) felt invisibility and (b) negative/positive affect. We find support for our predictions in a two-wave survey of 186 corrections officers (Study 1) and an experiment with 379 essential workers across a variety of industries (Study 2).